Prevalence of Dental Caries in 12-Year-Olds in San Pedro de Macorís, DR - Diaz-Nicolas, Jomar; Silva-Vetri, Maria Guadalupe; Rivas-Tumanyan, Sona; Toro, Milagros J.; Elías-Boneta, Augusto R. (Puerto Rico Health Sciences Journal, 2020)
Objective: Dental caries is one of the most prevalent chronic diseases in children. Currently, no data are available on dental caries prevalence in the Dominican Republic. The purpose of this study was to estimate the prevalence of dental caries in schoolattending 12-year-olds in San Pedro de Macorís, Dominican Republic. Methods: A cross-sectional epidemiological study using a probabilistic sample, stratified by type of school (public/private) and gender, was conducted. Two calibrated examiners conducted the evaluations of oral soft/hard tissues. Caries experience was summarized in terms of prevalence; the number of decayed, missing, and filled teeth (DMFT) and surfaces (DMFS); and the significant caries (SiC) index, in all the participants, and by gender and school type. Logistic and Poisson regression models were used to compare caries experience by sex and school type. Results: Four hundred and two 12-year-olds enrolled in 14 public and 11 private schools were evaluated. The overall dental caries prevalence was 73%. The mean DMFS was 3.87, the mean DMFT was 2.64, and the SiC index was 5.07. Girls had significantly higher mean DMFS, DMFT, and SiC indices than did boys. Public school attendees had significantly higher DMFS, DMFT, and SiC indices than did those children attending private schools. The decayed (D) component accounted for 71% of the DMFT value. Conclusion: The WHO’s goal of all 12-year-olds having a DMFT less than or equal to 3 was met by all the participants in our study. Girls and public-school attendees carry the burden of the disease. The high D component of the index suggests that there are unmet dental-caries needs. This information will assist in the design and implementation of future primary and secondary prevention programs.